About Scholarly Works in the Field of Islamic Economic Law: A Visualization of Related Topics - Ahmad Abbas; Manswab Mahsen Abdulrahman (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2023)
Understanding issues raised in academic literature is a critical step in developing scholarly works in the field of Islamic economic law. This study aims to explore the topics and trends in the field of Islamic economic law in the last three decades, from 1992–2021. The data used in this study were online published articles from 1992 to 2021. Harzing’s Publish or Perish (PoP), VOSViewer, and Open Knowledge Maps were tools utilized for processing and analyzing the data. 169 articles were retrieved by applying the keyword and title word "Islamic Economic Law" in the Google Scholar database. The result of the study shows an increasing trend in the publication of scholarly works for the past thirty years, with 645 citations. As a result of the visualization, the topic of Islamic economic law tends to be designed in the context of theory, implementation through a case study approach, perspectives, a paper review elaborating the contract, and research in the field of Islamic law for economics. Islamic economic law areas recently attract an increasing number of attention from scientists, so related topics can be developed wider by various methods.